2006
DOI: 10.1021/jf052843l
|View full text |Cite
|
Sign up to set email alerts
|

Herbicidal Potential of Ophiobolins Produced by Drechslera gigantea

Abstract: Drechslera gigantea, a potential mycoherbicide of grass weeds, was isolated in Florida from naturally infected large crabgrass (Digitaria sanguinalis); it produces phytotoxic metabolites in liquid culture. The main metabolite was identified by spectroscopic methods and optical properties as ophiobolin A (1), a well-known phytotoxic sesterterpene produced by several phytopathogenic fungi of important crops and already extensively studied for its interesting biological activities. The other three minor metabolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 30 publications
(45 reference statements)
6
95
0
1
Order By: Relevance
“…At concentrations ranging from 0.1 mM to 0.6 mM, degrees of lesions caused by some terpenoids and diketopyperazines obtained from other phytopathogenic fungi in their respective hosts 11,17,18 are very similar to those observed in the present work. Thus, as considered for those phytotoxins, the phytotoxic metabolites produced by A. euphorbiicola may be, in part, responsible for the virulence of this necrotrophic fungus against E. heterophylla.…”
Section: Resultssupporting
confidence: 85%
“…At concentrations ranging from 0.1 mM to 0.6 mM, degrees of lesions caused by some terpenoids and diketopyperazines obtained from other phytopathogenic fungi in their respective hosts 11,17,18 are very similar to those observed in the present work. Thus, as considered for those phytotoxins, the phytotoxic metabolites produced by A. euphorbiicola may be, in part, responsible for the virulence of this necrotrophic fungus against E. heterophylla.…”
Section: Resultssupporting
confidence: 85%
“…The isolate was maintained on potato dextrose agar plates until further processing. Mass culturing of the fungal isolate was carried out in M-1-D broth (growth medium) (Evidente et al, 2006b). This medium was autoclaved and inoculated with bits of mycelia and spores of D. rostrata and kept at 25 o C. After 28 days of growth, fungal cultures and their metabolites were subjected to further processing.…”
Section: Procurement and Incubation Of Fungal Isolatementioning
confidence: 99%
“…This compound was effective against Avena sativa (Kastanias and Chrysayi-Tokousbalides, 2005). Evidente et al (2006b) isolated and identified phytotoxic/ herbicidal constituents (e.g. ophiobolin A) from a fungus, Drechslera gigantea, which has herbicidal properties against many monocot and dicot weeds such as C. album.…”
Section: Introductionmentioning
confidence: 99%
“…Kastanias and Tokousbalides (2000) isolated pyrenophorol from a D. avenae pathotype that exhibited herbicidal potential against Avena sterilis L. Evidente et al (2005) reported that drazepinone, a trisubstituted tetrahydronaphthofuroazepinone from D. siccans, exhibited herbicidal activity against monocot weeds. In another study, Evidente et al (2006b) identified four herbicidal constituents from D. gigantea, viz. ophiobolin A, 6-epi-ophiobolin A, anhydro-6-epi-ophiobolin A, and ophiobolin I, which were very effective against several grass and broadleaf weeds.…”
Section: Laboratory Bioassaysmentioning
confidence: 99%